Portrayals of Pain in Children's Popular Media: Mothers' and Fathers' Beliefs and Attitudes - Pavlova, Maria; Mueri, Kendra; Kennedy, Madison; Wallwork, Sarah; Moseley, G. Lorimer; Jordan, Abbie; Noel, Melanie (Frontiers in Pain Research, 2022)
Evidence suggests that children's popular media may model maladaptive and distorted experiences of pain to young children. In a recent study, pain depicted in popular media targeting 4–6-year-olds was frequently and unrealistically portrayed, evoked little response or empathy from observing characters, and perpetuated unhelpful gender stereotypes. Parents play a critical role in both children's pain experiences and children's media consumption. Yet, no study to date has examined parents' beliefs and attitudes regarding how pain is portrayed in media for young children. The present study aimed to fill this gap by examining how parents perceive and appraise painful instances depicted in children's popular media. Sixty parents (48% fathers) of children aged 4 to 6 years completed a semi-structured interview to assess their general beliefs and attitudes toward how pain is portrayed in children's media. Inductive reflexive thematic analysis was conducted to identify and analyze key patterns in the data. Qualitative analyses generated two major themes representing parental beliefs regarding pain that is portrayed in children's media: “entertaining pain” and “valuable lessons”. Findings reveal that parents believe that pain portrayed in popular media serves either a function of entertaining and amusing children or can provide valuable lessons about appropriate emotional responses and empathic reactions. Further, pain portrayals could also instill valuable lessons and provide children with a point of reference and language for their own painful experiences. Parents serve as a primary socialization agent for young children; thus, it is important that parents remain aware of underlying messages about how pain is portrayed in children's popular media so that they can optimally discuss these portrayals, promote their children's pain education and understanding and positively impact future pain experiences.